1991
DOI: 10.1258/002367791780808446
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation within and between lines of diabetes-prone and non-diabetes-prone BB rats; allele distribution of 8 protein markers

Abstract: SummaryTwenty-four inbred and 2 outbred lines of the BB rat have been genetically characterized by establishing the allele distribution of 8 monogenic protein markers. The marker genes are: , glyoxalase I (010-1), group specific component (Oe), and haemoglobin-,g-chain (Hbb). At least 3 linkage groups are represented by this set of markers. Genetic variation was found both within and between lines. Within-line variation was observed in 4 lines, including the 2 outbred lines. The other 22 lines could be subdivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Firstly, spontaneous autoimmune diabetes was identified in 1974 in a Canadian colony and then led to the creation of two founder colonies from which all substrains have been derived including one of inbred Biobreeding Diabetes-Prone/Worcester (BBDP/Wor) and one of outbred Biobreeding Diabetes-Prone (BBDP) rats [22]. It was reported that immunologically and genetically distinct BB rat substrains were derived from several tertiary Biobreeding (BB) rat colonies [23] including Biobreeding/Ottawa Karlsburg (BB/OK) (BB/Pfd) and Biobreeding Spontaneously Hypertensive Rats (BB.SHR) [2427]. Additionally, BB rats resistant to diabetes have been bred to act as controls.…”
Section: Bb Ratsmentioning
confidence: 99%
“…Firstly, spontaneous autoimmune diabetes was identified in 1974 in a Canadian colony and then led to the creation of two founder colonies from which all substrains have been derived including one of inbred Biobreeding Diabetes-Prone/Worcester (BBDP/Wor) and one of outbred Biobreeding Diabetes-Prone (BBDP) rats [22]. It was reported that immunologically and genetically distinct BB rat substrains were derived from several tertiary Biobreeding (BB) rat colonies [23] including Biobreeding/Ottawa Karlsburg (BB/OK) (BB/Pfd) and Biobreeding Spontaneously Hypertensive Rats (BB.SHR) [2427]. Additionally, BB rats resistant to diabetes have been bred to act as controls.…”
Section: Bb Ratsmentioning
confidence: 99%
“…Comprehensive studies of microsatellite variation are available for less than 10% of inbred strains, and little additional information is available in the literature on other DNA polymorphisms, such as single-nucleotide polymorphisms (SNPs) or randomly amplified polymorphic DNA markers. 26 In the early 1990s, one of the more detailed studies in inbred diabetes-prone BB rats showed, by the application of simple protein markers, that these did indeed carry some heterozygotic traits, 27 and some years later DNA fingerprinting also showed genetic heterogeneity in inbred BALB/c mice. 28 Furthermore, it is well known that separation of rodent strains into separated subcolonies gives rise to phenotypic variation even though skin grafting between the subcolonies still does not lead to rejections.…”
mentioning
confidence: 99%
“…In humans and NOD mouse, the combined action of many MHC alleles with the non-MHC genes results in their diabetogenic action [ 28 , 63 ]. The BB rats are the most valuable experimental animals for studying the genetic basis of type 1 diabetes [ 64 ] and also in intervention studies [ 65 , 66 ]. This sort of rodent had been derived from the outbred Wistar rodents in which spontaneous hyperglycemia and ketoacidosis occurred in the 1970s period.…”
Section: Main Textmentioning
confidence: 99%